Perbandingan Cystatin C Serum dan Kreatinin Serum untuk Deteksi Cedera Ginjal Akut pada Pasien Sepsis di Ruang Rawat Intensif Rumah Sakit Haji Adam Malik Medan - Kurniawan, Heru; Hanafie, Achsanuddin; Mursin, Chairul M (Perdatin Pusat, 2014)
Perubahan mendadak laju filtrasi glomerulus (LFG) pada pasien sakit kritis dengan sepsis tidak diikuti secara paralel dengan perubahan kreatinin serum. Tujuan dari penelitian ini adalah membandingkan kegunaan dari cystatin C serum dan kreatinin serum sebagai penanda biologis fungsi ginjal pada pasien sepsis di ruang rawat intensif (RRI). Sebuah studi cross-sectional dilakukan pada pasien dewasa usia 18–65 tahun di RRI RSUP Haji Adam Malik. Kreatinin serum, cystatin C serum dan creatinin clearance (CrCl) 24 jam urin diobservasi pada 24 pasien sepsis. CrCl 24 jam urin yang disesuaikan dengan luas permukaan tubuh digunakan sebagai “baku emas” untuk menentukan LFG. Kreatinin serum, cystatin C serum dan CrCl 24 jam urin (nilai rata-rata ± standar deviasi [range]) adalah 1,53 ± 1,13 mg/dL (0,3–4,2 mg/dl), 1,71 ± 1,1 mg/L (0,6–4,48 mg/L), dan 66,33 ± 37,77 ml/min/1,73 m2 (4–137 mL/min/1,73 m2). 17 dari total 24 pasien mengalami CGA. Cystatin C serum memilki nilai sensitivitas dan spesifisitas sebesar 82,4% dan 85,7%. Sedangkan kreatinin serum memiliki nilai sensitivitas dan spesifisitas sebesar 52,9% dan 85,7%. Cystatin C secara diagnostik lebih superior dibandingkan kreatinin serum dengan area under the curve (AUC) 0,874 untuk cystatin C serum dan 0,785 untuk kreatinin serum. Cystatin C serum dengan nilai cutt-off 1,03 mg/L dan kreatinin serum dengan cutt-off 1,0 mg/dL memiliki sensitivitas dan spesifisitas yang sama yaitu 82,4% dan 85,7%. Cystatin C adalah penanda biologis yang akurat dalam mendeteksi perubahan akut pada LFG, dan terbukti lebih superior dibandingkan kreatinin serum dalam mendiagnosa CGA pada pasien sakit kritis. Kata Kunci: Cedera ginjal akut, creatinin clearance 24 jam urin, cystatin C serum, kreatinin serum, sepsis Comparative of Serum Cystatin C and Serum Creatinin for Detection Acute Kidney Injury on Septic Patients in Icu Haji Adam Malik Hospital Medan Sudden changes in glomerular filtration rate (GFR) septic critically ill patients are not instantly followed by parallel changes in serum creatinine. The aim of the present study was to compare the utility of serum cystatin C and serum creatinin as a marker of renal function in these patients.A cross-sectional study was conducted in adult patients among 18-65 years in the intensive care unit Haji Adam Malik hospital. Serum creatinine, serum cystatin C and 24-hour creatinine clearance (CrCl) were observed in 24 critically ill patients with sepsis. Twenty-four-hour body surface adjusted CrCl was used as a control because it is the ‘gold standard’ for determining GFR.Serum creatinine, serum cystatin C and CrCl (mean ± standard deviation [range]) were 1.53 ± 1.13 mg/dL (0.3–4.2 mg/dl), 1.71 ± 1.1 mg/l (0.6–4.8 mg/l), and 66.33 ± 37.77 mL/min per 1.73 m2 (4–137 mL/min per 1.73 m2), respectively. Of the total 24 patients, 17 patients had AKI. Serum cystatin C has a sensitivity of 82,4% and spesificity value of 85,7%. Serum creatinin has a sensitivity and spesificity value of 52,9% and 85,7%. Cystatin C was diagnostically superior to creatinine (area under the curve [AUC] for cystatin C 0.874 and for creatinine 0,785. Serum cystatin C with cutt-off value 1,03 mg/L and serum creatinin with cutt-off value 1,0 mg/dl has the same sensitivity and spesificity of 82,4% and 85,7%, respectively. Cystatin C is an accurate marker of subtle changes in GFR, and it may be superior to creatinine when assessing this parameter in clinical practice in critically ill patients. Key words: Acute kidney injury, serum creatinin, serum cystatin C, sepsis24-hour creatinine clearance Reference 1. Bagshaw SM, George C, Bellomo R. Changes in the incidence and outcome forearly acute kidney injury in a cohort of Australian intensive care units. Crit Care.2007;11:R68.2. Hoste EA, Clermont G, Kersten A. RIFLE criteria for acute kidney injury areassociated with hospital mortality in criticallyill patients: A cohort analysis. CritCare. 2006;10:R73.3. Mehta RL, Pascual MT, Soroko S. Spectrum of acute renal failure in the intensivecare unit: The PICARD experience. Kidney international. 2004; 66:, 1613–21.4. Uchino S, Kellum JA, Bellomo R.Acute renal failure in critically ill patients:A multinational, multicenter study. JAMA. 2005;294:813–8.5. Uchino S, Bellomo R, Goldsmith D: Anassessment of the RIFLE criteria for acuterenal failure in hospitalized patients. Critcare. 2006;34:1913–7.6. Doi K, Peter ST, Eisner C. Reduced production of creatinine limits its use as a marker of kidney injury in sepsis. J Am Soc Nephrol. 2009;20:1217–21.7. Abrahamson M, Olafsson I, Palsdottir A, Ulvsback M, Lundwall A,Jensson O, dkk. Structure and expression of the humancystatin C gene. Biochem J. 1990;268:287–94.8. Spahillari A, Parikh CR, Sint K, Koyner JL, Patel UD, Edelstein CL, dkk. Serum cystatin C- versus creatinine-based definitions of acute kidney injury following cardiac surgery: a prospective cohort study. Am J Kidneys Dis. 2012;60:922–9.9. Slort PR, Ozden N, Pape L, Offner G, Tromp WF, Wilhelm AJ, dkk. Comparing cystatin C and creatinine in the diagnosis of pediatric acute renal allograft dysfunction. Pediatr Nephrol. 2012;27:843–9.10. Chung MY, Won Jun D, Sung SA. Diagnostic value of cystatin C for predicting acute kidney injury in patients with liver cirrhosis. KASL. 2010; 16: 301–7.11. Le Bricon T, Leblanc I, Benlakehal M, Gay-Bellile C,Erlich D, Boudaoud S. Evaluation of renal function inintensive care: plasma cystatin C vs. creatinine andderived glomerular filtration rate estimates. Clin Chem. 2005;43:953–7.